Making body work sequences visible: an ethnographic study of acute orthopaedic hospital wards. Issue 5 (15th April 2020) - Backhouse, Tamara; Hammond, Simon P.; Cross, Jane L.; Lambert, Nigel; Varley, Anna; Penhale, Bridget; Fox, Chris; Poland, Fiona
Abstract: Within health and social care, academic attention is increasingly paid to understanding the nature and centrality of body work. Relatively little is known about how and where body work specifically fits into the wider work relations that produce it in healthcare settings. We draw on ethnographic observations of staff practice in three National Health Service acute hospital wards in the United Kingdom to make visible the micro‐processes of patient care sequences including both body work and the work contextualising and supporting it. Our data, produced in 2015, show body work interactions in acute care to be critically embedded within a context of initiating, preparing, moving and restoring and proceeding. Shades of privacy and objectification of the body are present throughout these sequences. While accomplishing tasks away from the physical body, staff members must also maintain physical and cognitive work focussed on producing body work. Thus, patient care is necessarily complex, requiring much staff time and energy to deliver it. We argue that by making visible the micro‐processes that hospital patient care depends on, including both body work and the work sequences supporting it, the complex physical and cognitive workload required to deliver care can be better recognised. (A virtual version of this abstract is available at: https://www.youtube.com/channel/UC_979cmCmR9rLrKuD7z0ycA )